Roadmap to economically viable hydrogen liquefaction. (11th May 2017) - Cardella, U.; Decker, L.; Klein, H.
Abstract: The distribution of hydrogen in liquid state has several advantages because of its higher volumetric density compared to compressed hydrogen gas. The demand for liquid hydrogen (LH2 ), particularly driven by clean fuel cell applications, is expected to rise in the near future. Large-scale hydrogen liquefaction plants will play a major role within the hydrogen supply chain. The barriers of built hydrogen liquefiers is the low exergy efficiency and the high specific liquefaction costs. Exergy efficiency improvements, however, are limited by economic viability. The focus of this paper is to present a roadmap for the scale-up of hydrogen liquefaction technology, from state-of-the-art plants to newly developed large-scale liquefaction processes. The work is aimed at reducing the specific liquefaction costs by finding an optimal trade-off between capital costs and operating costs. To this end, two developed hydrogen liquefaction processes were optimized for specific energy consumption and specific liquefaction costs, showing the potential to reduce the specific liquefaction costs by 67% for a 100 tpd LH2 plant compared to a conventional 5 tpd LH2 plant while achieving a specific energy consumption between 5.9 and 6.6 kWh per kg LH2 with technology that is or will be available within 5 years. The results make liquid hydrogen a viable distribution route for hydrogen for mobility. Highlights: A roadmap for stepwise implementation of large hydrogen liquefiers is proposed. New liquefaction processes are optimized in efficiency and total cost of ownership. Specific energy consumption between 5.9 and 6.6 kWh per kg LH2 within 5 years. Specific liquefaction costs reduced by about 60% by upscaling from 5 to 50 tpd. Results make liquid hydrogen a viable distribution route for hydrogen mobility.